PENGARUH METODE LATIHAN DRILL TERHADAP KETERAMPILAN PASSING SEPAKBOLA PADA PESERTA DIDIK EKSTRAKURIKULER DI SMA NEGERI 8 PONTIANAK - Mahfan Rivai; Ahmad Atiq; Andika Triansyah (Universitas Tanjungpura, 2019)
Abstract The problem in this study was whether the effect of drill training methods on soccer passing skills on extracurricular students in Pontianak 8 high school. This study aimed to determine the effect of drill training methods on soccer passing skills on extracurricular learners at Pontianak 8 High School. The method used was the experimental method, the study design used pre-experimental design, and the study design used the design of one group pretest-posttest design. The research sample was group 2 of 25 students. The data analysis technique used is descriptive analysis and using the t-test (influence test).From the results of the research conducted, it can be concluded that there was an effect of the drill training method on soccer passing skills on extracurricular students at Pontianak 8 High School. The results of the t-test analysis showed that the values of tcount (10.09) and ttable (2,064) or (10.09> 2,064). The research data also showed that most students experience an increase in football passing results after being treated through drill method activities.Keywords: Method Of Drill Training, Soccer Passing.